Syndromes of Head and Neck – A Quick Review - Sangeetha Priya.P1 , Aravindha Babu2 , K.M.K.Masthan3 , N.Anitha4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The aggregate of signs and symptoms associated with any morbid process and constituting together thepicture of the disease and related to each other anatomically, biologically and physiologically. A group ofdeformation and malformation sequence etc that occurs together due to some identifiable underlying cause.The aim of this review is to describe a collective knowledge about various syndromes associated head andneck- A dentist point of view